White-rotting fungus with clamp-connections in a coniferous wood from the Lower Cretaceous of Heilongjiang Province, NE China. (January 2020) - Tian, Ning; Wang, Yongdong; Zheng, Shaolin; Zhu, Zhipeng
Abstract: Fossil fungi are very important components for shaping the paleoecosystem, but they are rarely documented in the geological record. Here we report a well-preserved fossil mycelium consisting of clamp-bearing septate hyphae in a petrified coniferous wood ( Cupressinoxylon baomiqiaoense Zheng et Zhang) from the Lower Cretaceous Yunshan Formation in Heilongjiang Province, NE China. The fungal hyphae, with a diameter of ca. 2.5 μm, are tubular in shape with septa and clamp–connections. Taxonomically, the nature and occurrence of typical clamp–connections indicate that the present fungal remains be referred to the Basidiomycota. Ecologically, this fossil mycelium is proposed to be a saprotroph, i.e., a wood rotting fungus. The wood decay symptoms of the wood host strongly indicate that the present fungal mycelium to be a white-rotting fungus. This fossil mycelium represents the first fossil fungal record from the Cretaceous of Northeast China, and provides further evidence for investigating the plant-fungal interaction in the Cretaceous terrestrial ecosystem.